PRINT ADVERTISING COPY TESTING: SOME PROBLEMS IN VALIDITY - Eduardus Tandelilin (Journal of Indonesian Economy and Business (JIEB), 1995)
This article aims to develop an integral overview of the present status of thetheory of the copy testing validity. It includes the presentation of the theoriticalconsideration or conceptual issues in copy testing, some empirical results or findingin copy testing, and finally, proposes an alternative conceptual framework of copytesting that a company can use to improve validity in copy testing especially in printcopy testing.